SERPENT-Brasil: a technological tool for snakebite management - de Almeida Gonçalves Sachett, Jacqueline; dos Santos Costa Rocha, Gisele; Silva, Elisangela; da Cunha Marques, Anne Grace Andrade; Bisneto, Pedro Ferreira; Pereira, Handerson Silva; da Silva, Victor Carlos Pardo Ratis; Carvalho, Kathleen Maclenny Pereira; Silva, Lincoln Luís; Pucca, Manuela Berto [UNESP]; Monteiro, Wuelton Marcelo (Pan American Health Organization, 2025)
Objective: To report on the development and features of a mobile application (app) to guide the public and health professionals on pre-hospital emergency measures after snake envenomation. Methods: This was a four-stage methodological study conducted from June 2020 to July 2022. The app development included creating a mobile resource to guide pre-hospital care and to direct victims to hospitals that have antivenom. Results: The SERPENT-BRASIL app was developed for use on Android and IOS devices with an intuitive interface. It offers online and offline access to information on hospitals and mapping routes via Google Maps. In addition, it allows users to report snake sightings and to request emergency rescue. Conclusion: The SERPENT-BRASIL app improves snakebite management and prevention, eases the burden on health services, and promotes health education. Collection of snake envenomation data contributes to public safety, making the app an essential resource for public safety in Brazil.